The complete chloroplast genome of the national tree of Peru, quina (Cinchona officinalis L., Rubiaceae) - Arbizu Berrocal, Carlos Irvin (2021)
Here, we report the first complete chloroplast (cp) genome of Cinchona officinalis. This cp genome has a 156,984 bp in length with typical quadripartite structure, containing a large single copy (LSC) region (83,929 bp) and an 18,051 bp small single-copy (SSC) region, separated by two inverted repeat (IR) regions (27,502 bp). The total GC content was 37.75%. Quina tree chloroplast genome possesses 135 genes that consisted of 89 protein-coding genes, 37 tRNA, eight rRNA, and one pseudogene. Phylogenetic analysis showed that C. officinalis is sister to C. pubescens and sister to them is Isertia laevis; all belong to the Cinchonoideae sub-family.